Efficient Mapping XML DTD to Relational Database - Mohammed Adam Ibrahim, Fakharaldien; Khalid, Edris; Jasni, Mohamad Zain; Norrozila, Sulaiman (Science and Engineering Research Support soCiety (SERSC), 2012)
Mapping XML documents into relational database is a promising solution because relational databases are mature and scale very well and they have the advantages that in a relational database XML data and structured data can coexist making it possible to build application that involve both kinds of data with little extra effort. In this paper, we propose two algorithms (XRD, XRS) that maps XML documents into relational database. The algorithm steps are given in details to describe how to map the XML documents into relational database. Then we report our experimental results on a real database to show the performance of our method in some features.